A consensus statement for the clinical use of the renal sodium-glucose co-transporter-2 inhibitor dapagliflozin in patients with type 2 diabetes mellitus. Issue 7 (3rd July 2017) - Avogaro, A.; Giaccari, A.; Fioretto, P.; Genovese, S.; Purrello, F.; Giorgino, F.; Del Prato, S.
ABSTRACT: Introduction : The present review developed a clinical consensus based on a Delphi method on Dapagliflozin, a selective inhibitor of the renal sodium-glucose co-transporter-2 (SGLT2-I) in the treatment of patients with Type 2 diabetes mellitus. Areas covered : Panel members, using a 5-point scale, were asked to rate 9 statements on pharmakodinamic, mode of action on glycaemic and extra-glycaemic effects, and safety of dapaglifozin, Members also aimed to identify the patient most susceptible to the treatment with dapagliflozin . Expert commentary : Dapagliflozin is effective in lowering the plasma glucose concentration with a good safety profile. Dapagliflozin can be utilized in combination with all other antihyperglycaemic agents at all stages of the disease: however, a reduced GFR limits its efficacy. As for the other drugs of the class, Dapagliflozin positively modifies other risk factors for CV disease: these effects will be tested in the so far largest cardiovascular outcome trial for the SGLT2 inhibitors so far, the DECLARE trial, which will communicate whether this class of drugs will be disease-modifier in patients with type 2 diabetes also in primary prevention.